1989
DOI: 10.2337/diab.38.5.569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aldose Reductase Inhibitor Sorbinil on Neuroaxonal Dystrophy and Levels of myo-inositol and Sorbitol in Sympathetic Autonomic Ganglia of Streptozocin-Induced Diabetic Rats

Abstract: Biochemical and ultrastructural effects of the aldose reductase inhibitor sorbinil were examined in two experimental rat models of chronic diabetic neuropathy: rats with streptozocin-induced diabetes (STZ-D) and rats fed a galactose-enriched diet. The frequency of neuroaxonal dystrophy in the superior mesenteric sympathetic ganglia of rats with untreated 8-mo STZ-D increased sevenfold compared with that in age-matched controls. Animals chronically maintained on a diet containing 50% galactose, however, did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Yip, and R.G. Tilton, unpublished observations) or ultrastructural features of neuroaxonal dystrophy (14) in the sympathetic ganglia of galactosemic rats compared to animals with chronic diabetes. Recently, other studies have demonstrated a number of differences between galactosemic and diabetic rats (55).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Yip, and R.G. Tilton, unpublished observations) or ultrastructural features of neuroaxonal dystrophy (14) in the sympathetic ganglia of galactosemic rats compared to animals with chronic diabetes. Recently, other studies have demonstrated a number of differences between galactosemic and diabetic rats (55).…”
Section: Discussionmentioning
confidence: 90%
“…Aldose reductase inhibitors have been found to prevent and, in some cases, reverse abnormalities in sciatic nerve Na + -K + -ATPase activity, axonal transport, and nerve conduction velocity in experimental diabetes (27)(28)(29)(30). Although most of these studies have concentrated on somatic myelinated nerves, a few studies have suggested that there is an effect on biochemical (45), pathophysiological, and structural histopathology (14) involving the autonomic nervous system as well. In our TOH experiments, only a small effect of sorbinil, if any, was detectable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, we showed that biochemical and ultrastructural alterations in the sympathetic ganglia of chronically diabetic rats were substantially improved, but not normalized, by initiation of sorbinil treatment at the time of induction of diabetes (30). However, it would be more clinically relevant to examine the ability of aldose reductase therapy to reverse established ultrastructural lesions in experimental diabetic animals.…”
mentioning
confidence: 94%
“…However, the accumulation of sorbitol and variable decrease in myo-inositol, which have been described in sympathetic ganglia in STZ-D rats (29,30), suggested a role for aldose reductase inhibitors in the treatment of autonomic neuropathy. Several clinical (31)(32)(33) and experimental animal (29,34,35) studies have demonstrated improvement of selected biochemical and physiological parameters of autonomic nervous system function in response to aldose reductase inhibitors.…”
mentioning
confidence: 96%